Jamaica under Manley : dilemas of socialism and democracy - Kaufman, Michael (Lawrence Hill ConnecticutUS, 1985)
Comments on the economic and political hurdles that confronted Manley's PNP government during 1972-80. Describes the economic conditions during the pre and post emancipation period. Examines the bauxite industry and the problems associated with foreign control of the industry. Summarizes the social and political tradition of the classes in Jamaican society and their differing ideologies. Discusses the structural weaknesses of the Jamaican economy which were outside the control of the PNP examining the PNP's response to these weaknesses, the strategies and tactics adopted and the viability of the various alternatives.